2009
DOI: 10.1080/10910340903454922
|View full text |Cite
|
Sign up to set email alerts
|

Surface Integrity Characterization and Prediction in Machining of Hardened and Difficult-to-Machine Alloys: A State-of-Art Research Review and Analysis

Abstract: This paper presents a review of the state-of-art research on surface integrity characterization, especially the characteristics of residual stresses produced in machining of hardened steels, titanium and nickel-based superalloys using the geometrically defined tools. The interrelationships among residual stresses, microstructures, and tool-wear have been discussed. Current research on residual stress modeling and simulation using finite element method has been critically assessed. Also, the rationale for devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(79 citation statements)
references
References 80 publications
0
78
0
1
Order By: Relevance
“…However, machining these alloys poses a challenge due to the high temperatures generated during cutting as a result of intensive adhesion of the workpiece material to the tool surface. These characteristics make titanium alloys difficult-to-machine materials [2]. One of the most crucial issues of cutting tool behavior during machining of Ti is the low efficiency of the most widely used PVD coating such as TiAlN.…”
Section: Introductionmentioning
confidence: 99%
“…However, machining these alloys poses a challenge due to the high temperatures generated during cutting as a result of intensive adhesion of the workpiece material to the tool surface. These characteristics make titanium alloys difficult-to-machine materials [2]. One of the most crucial issues of cutting tool behavior during machining of Ti is the low efficiency of the most widely used PVD coating such as TiAlN.…”
Section: Introductionmentioning
confidence: 99%
“…There are few researchers working on the methods of prediction and prevention of residual stresses [16]. El-axir deals with the method of modeling residual stress distribution in turning for different materials showed that the residual stress [17].…”
Section: Effect Of Residual Stressmentioning
confidence: 99%
“…A comprehensive literature review comprising behavior of residual stresses generated after conventional machining processes is presented by Gue et al [9] in which mostly hard-to-cut metals are discussed. Rao et al [22] determined residual stresses in Aluminum alloy 2014 T6 after EDM for the discharge current of 10 and 12 ampere, and this study was limited to surface.…”
Section: Introductionmentioning
confidence: 99%